Drosophila Exhibit Divergent Sex-Based Responses in Transcription and Motor Function After Traumatic Brain Injury - Shah, Ekta J.; Gurdziel, Katherine; Ruden, Douglas M. (Frontiers in Neurology, 2020)
Every year, millions of people in the US suffer brain damage from mild to severe traumatic brain injuries (TBI) that result from a sudden impact to the head. Despite being a leading cause of death and disability worldwide, sex differences that contribute to varied outcomes post-injury are not extensively studied and therefore, poorly understood. In this study, we aimed to explore biological sex as a variable influencing response to TBI using Drosophila melanogaster as a model, since flies have been shown to exhibit symptoms commonly seen in other mammalian models of TBI. After inflicting TBI using the high-impact trauma device, we isolated w1118 fly brains and assessed gene transcription changes in male and female flies at control and 1, 2 and 4 hours after TBI. Our results suggest that overall, Drosophila females show more gene transcriptional changes related to immune response and mitochondrial activity than males with some genes exhibiting a phasic change in transcription. We also looked at the impact of injury on mitochondrial health and motor function in both sexes before and after injury. Although, both sexes report similar levels of mitochondrial oxidation, males fare worse than females on behavioral outcome measures. We observed faster recovery in locomotor and climbing ability in females whereas males exhibit bimodal recovery. These data suggest that sex-differences not only influence the response to TBI but also contribute to varied outcomes post-injury.